Isolation and Antimicrobial Activity of Endophytic Fungi on Avicennia marina and Sonneratia alba Mangroves in Mengkapan Village, Sungai Apit District, Siak Regency - Esti Nur Rahayu; Efriyeldi Efriyeldi; Ummi Mardhiah Batubara (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2024)
This research was conducted from February to June 2023. A sampling of Avicennia marina and Sonneratia alba mangroves was conducted in the mangrove ecosystems of Mengkapan Village, Sungai Apit District, Siak Regency. This research aims to identify the species and test the antimicrobial activity of endophytic fungi found in the leaves and stems of A. marina and S. alba mangroves in the mangrove ecosystem of Mengkapan Village using survey and experimental methods. This research began by determining the sampling location and measuring the physical and chemical parameters of the mangrove environment. Then, sampling and preparation of A. marina and S. alba mangrove samples were carried out to isolate the endophytic fungi. After isolation, macroscopic and microscopic characterization was done to identify endophytic fungi. The diameter increase of the endophytic fungi was measured and calculated, and the antagonism activity test of the endophytic fungi was carried out. The antimicrobial index of endophytic fungi was measured against the pathogenic bacteria Vibrio sp and E. coli. This research obtained that 12 endophytic fungi were isolated from the mangroves A. marina and S. alba: two genera Rosellinia, two genera Pythium, four genera Hansfordia, and four genera Aspergillus. Based on the test results, all genera found in this research inhibited the growth of E. coli with inhibitions of 75.99% (Rosellinia sp), 87.70% (Pythium sp), 73.42% (Hansfordia sp) and 86.88% (Aspergillus sp). However, only three genera inhibited the growth of Vibrio sp by more than 50%, with inhibitions of 85.23% (Rosellinia sp), 87.87% (Hansfordia sp), and 86.07% (Aspergillus sp).